PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI APARATUR SIPIL NEGARA PADA DINAS LINGKUNGAN HIDUP KABUPATEN PONOROGO - Mubarok, Riza Budi; Kurniawanto, Hudi; Sriwidodo, Untung (Universitas Slamet Riyadi, 2019)
The general purpose of this study was to examine and analyze the influence of leadership style, and organizational commitment on performance, with work motivation as a mediating variable ASN at the Environmental Agency of Ponorogo Regency. Specific objectives are to test and analyze: (1) the influence of leadership style on work motivation, (2) the influence of organizational commitment on work motivation, (3) the influence of leadership style on performance, (4) the effect of commitment on performance, (5) influence of motivation work on performance, (6) the influence of leadership style on performance with work motivation as a mediating variable, and (7) the effect of organizational commitment on performance with work motivation as a mediating variable. The population in this study were all ASN Ponorogo Regency Environmental Services as many as 89 people. In this study using the census method. This research data is primary data by filling out the questionnaire by respondents. After the data has been collected, an instrument test consisting of the validity test and the reliability test with Cronbach Alpha. Then F test, R2 test, hypothesis test are performed. Analysis techniques using linear regression, path analysis, and multiple tests. The results showed that (1) leadership style no significant effect on work motivation, (2) the influence of positive and significant organizational commitment on work motivation, (3) leadership style no significant effect on performance, (4) the effect of positive and significant commitment to performance, (5) the effect of positive and significant work motivation on performance, (6) the effect of positive and significant leadership style on performance with work motivation as a mediating variable, and (7) organizational commitment no significant effect on performance mediated by work motivation.